Promoting a Heritage Sports Tourism Place Strengthens Loyalty to Tourist Destination: The Case of Ancient Olympia in Greece - Christos C. FRANGOS; Pericles DIMITROPOULOS; Konstantinos C. FRAGKOS; Athina SOTIROPOULOU; Ele PASHALI; Christina LITSI (Communications of International Proceedings, 2020)
The ancient Olympia is the birthplace of Olympic Games which have started on 776B.C. in Greece. Ancient Olympia was, also, a place for the worship of Zeus, the Head of the 12 Gods in ancient Greece. Relevant research includes the papers of The Temple of Zeus was the largest and most important building at Olympia and was one of the largest Doric temples in Greece.  The statue of Zeus within the temple was made by Pheidias (who had worked on the Parthenon and its statue of Athena) and was a solid gold and ivory representation of Zeus seated on a throne. It was regarded as one of the Seven Wonders of the Ancient World. Every four years the modern Olympic games are taking place in a city around the World and in the place of ancient Olympia in Greece the lightning ceremony is taking place for the lightning of the Olympic flame. Although the Ancient Olympia is a world-famous heritage sports place, few attempts have been made to market this place as an important tourist destination and to increase the loyalty of tourists visiting it. In this paper we attempt to describe the ruins of ancient Olympia, the buildings, the stadium and the history of the Olympic games. We define and we review critically an alternative kind of tourism, the heritage sports tourism. We find some weaknesses in the accessibility of ancient Olympia as a tourist destination. Finally, we suggest some improvements in the image of the tourist destination of ancient Olympia employing the immense power of Social Media and some ways of improving the accessibility to this important place of Greece.
Keywords: Ancient Olympia; Loyalty; Satisfaction; Promotion of tourist destination.